Students’ perception on School to Work transition during the SARS-CoV 2 pandemic - Simona NICOLAE; Ioana-Ruxandra LIE (Communications of International Proceedings, 2021)
The education market and the labor market are the two basic pillars of the development and progress of any economy. The SARS-CoV 2 pandemic caused in each of these markets major imbalances and led to rapid changes in the lives of all the stakeholders in these domains. The aim of this study is to find if and how POLITEHNICA (UPB) students’ perception on education, professional future and well-being has changed because of the economic and sanitary crisis. In order to achieve this goal, a self-administered questionnaire was used, and data was analyzed using descriptive statistics instruments. We found that students value their professors and the information they provide, and also the diploma they will receive after graduation, but they feel vulnerable to economic crises. We conclude with the main findings of our study and their implications, and further directions to assess this issue.
Keywords: SARS-CoV 2 pandemic; labor market; education; students’ perception; well-being.